Effect of Weak Acid Hypochlorous Solution on Selected Viruses and Bacteria of Laboratory Rodents - Takimoto, Kazuhiro; Yamada, Yasuko K.; Taharaguchi, Motoko; Zamoto-Niikura, Aya (EXPERIMENTAL ANIMALS, 2014)
Weak acid hypochlorous solution (WAHS) is known to have efficacy for inactivating pathogens and to be relatively safe with respect to the live body. Based on these advantages, many animal facilities have recently been introducing WAHS for daily cleaning of animal houses. In this study, we determined the effect of WAHS in inactivating specific pathogens of laboratory rodents and pathogens of opportunistic infection. WAHS with an actual chloride concentration of 60 ppm and a pH value of 6.0 was generated using purpose-built equipment. One volume of mouse hepatitis virus (MHV), Sendai virus, lymphocytic choriomeningitis virus, Bordetella bronchiseptica, Pasteurella pneumotropica, Corynebacterium kutscheri, Staphylococcus aureus, and Pseudomonas aeruginosa was mixed with 9 or 99 volumes of WAHS (×10 and ×100 reaction) for various periods (0.5, 1, and 5 min) at 25°C. After incubation, the remaining infectious viruses and live bacteria were determined by plaque assay or culture. In the ×100 reaction mixture, infectious viruses and live bacteria could not be detected for any of the pathogens examined even with the 0.5-min incubation. However, the effects for MHV, B. bronchiseptica, and P. aeruginosa were variable in the ×10 reaction mixture with the 0.5- and 1-min incubations. Sufficient effects were obtained by elongation of the reaction time to 5 min. In the case of MHV, reducing organic substances in the virus stock resulted in the WAHS being completely effective. WAHS is recommended for daily cleaning in animal facilities but should be used properly in order to obtain a sufficient effect, which includes such things as using a large enough volume to reduce effects of organic substances.